Corporate governance and ownership structure on performance - Paulina, Julinta; Barus, Imelda (Priviet Social Sciences Journal, 2022)
The aim of this study is to investigate how Corporate Governance structures, Related Party Transactions, and Family Ownership could influence Firm Performance in Indonesia. The data is collected from companies listed in LQ45 index from 2016 to 2018. Multiple regression analysis is used to examine the relationship between Corporate Governance, Related Party Transaction and Family Ownership towards Firm Performance, specifically on ROE. Corporate Governance can be measured by Independent Directors and Board Size in which the ratio of independent directors to the total of directors in the board whereas Board Size is the number of members sitting on the board. For Related Party Transaction, the measurements used is by utilizing the total amount of related party transactions by total of assets. Dummy variable will be used to indicate a Family Ownership, that is whether there is an affiliation member in the board. If there is a family member in the board, this will indicate as 1, and if there is no family member in the board, it will be indicated as 0. ROE is used to measure Firm Performance, that is net income divided by shareholder’s equity. The results concluded that only Independent Directors have positive significant to Firm Performance. Due to Independent Directors have higher control compare to other directors. This indicates the level of supervision of the company will also certainly increase which implies whenever a firm company is well monitored it will improve the firm performance especially the profit factor measured, i.e. ROE.